The Relationship Between Empathetic Classroom Climate And Students' Success - Bozkurt, Tülay; YILDIRIM, MELİS SERAY ÖZDEN (Elsevier Science Bv, Sara Burgerhartstraat 25, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2010)
This is a preliminary study leading to cultural definitions of empathetic behaviours and attitudes of teachers in education settings. Data were collected from among 497 students from the 6th and 11th classes of Kultur Schools and the departments of Psychology, Mathematics-Computer, and Business Administration at Kultur University. An empathy scale was developed based on a qualitative pilot study to explore behaviours and attitudes of teachers perceived as empathetic by reports of 100 students. The most important finding of the study is that empathetic behaviours rather than academic competencies of teachers have impact on self report students' success. The study underlined the importance of empathy as a crucial motivational concept to be taken into consideration in student-centered educational systems. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Empathy; empathetic behaviour; empathetic classroom climate; student success; Empati; empatik davranış; empatik sınıf ortamı; öğrenci başarısı